Pedogenic nodule stable isotope values from Wasatch Formation of southwest Wyoming, U.S.A - Brady Z Foreman; Ross Secord; Vera Korasidis (PANGAEA, 2024)
The data contained herein are stable carbon and oxygen isotope measurements from pedogenic carbonate nodules, which are early Paleogene in age. Pedogenic carbonate nodules analyzed herein were derived from the Wasatch Formation, which is exposed in the badlands outside the towns of La Barge and Big Piney, Wyoming in the United States of America. Several seasons of fieldwork in the area focused on recovery of these samples from the outcrops. These samples were obtained from a stratigraphic section focused at GPS N42.47377° W110.35292° (WGS84 datum). Pedogenic nodules were obtained from paleosol deposits within the geologic formation and excavated in situ using pick axe and shovel. Sampling and isotopic analysis occurred in 2015. Individual nodules were cut using a rock saw and polished using a diamond lap wheel in the Department of Earth and Atmospheric Sciences at the University of Nebraska-Lincoln. Micrite and sparite phases were identified and sampled using a binocular microscope and mounted dental drill. Stable carbon and oxygen determinations were performed at the University of Michigan Stable Isotope Laboratory using a Thermo Finnigan MAT 253 stable isotope ratio mass spectrometer with an attached Kiel IV automated preparation device. Precision is better than +/- 0.1 per mille for carbon and oxygen based on in-house standards. Isotope values are reported in standard delta notation relative to Vienna Pee Dee Belemnite (VPDB) standard. The underlying goal of the data collection was to identify the negative stable carbon isotope excursion associated with the Paleocene Eocene Thermal Maximum (PETM), a global climatic event that occurred ~56 million years ago. This event is associated with a global perturbation of the carbon cycle that is recognizable in both marine and nonmarine proxies. Pedogenic carbonate nodules (i.e., semi-spherical, authigenic calcite growths) have been found to faithfully preserve this carbon cycle perturbation in other basins.